2010
DOI: 10.1891/0886-6708.25.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Classes of Childhood Sexual Abuse and Women’s Adult Couple Relationships

Abstract: The current study assessed if childhood sexual abuse (CSA) can be meaningfully classified into classes, based on the assumption that abuse by a close family member differs in important ways from other abuse, and whether abuse classes were differentially associated with couple relationship problems. The childhood experiences and adult relationships of 1335 Australian women (18-41 years) were assessed. Latent class analysis identified three classes of CSA: that perpetrated by a family member, friend, or stranger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 56 publications
1
16
0
Order By: Relevance
“…In the SEM analyses, CSA severity was operationalized by three characteristics of the sexual experience which were used as indicators of a latent factor: the chronicity of abuse, the type of act perpetrated, and the relationship with the perpetrator. These characteristics were coded so that a high score indicated a greater severity of the abuse as suggested by current literature considering these characteristics (Watson & Halford, 2010;Whisman, 2006). Chronicity of abuse represented the number of times the abuse occurred and was coded from 0 (nonvictim), 1 (one time), 2 (two to five times), to 3 (more than five times).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the SEM analyses, CSA severity was operationalized by three characteristics of the sexual experience which were used as indicators of a latent factor: the chronicity of abuse, the type of act perpetrated, and the relationship with the perpetrator. These characteristics were coded so that a high score indicated a greater severity of the abuse as suggested by current literature considering these characteristics (Watson & Halford, 2010;Whisman, 2006). Chronicity of abuse represented the number of times the abuse occurred and was coded from 0 (nonvictim), 1 (one time), 2 (two to five times), to 3 (more than five times).…”
Section: Methodsmentioning
confidence: 99%
“…Child sexual abuse (CSA) survivors form a heterogeneous population and it is now well-established that the short-and long-term course of these experiences vary according to personal/familial pre-traumatic vulnerabilities, the nature and severity of the abuse and the quality of familial, social and professional support offered to the survivors (e.g., Godbout, Briere, Lussier, & Sabourin, 2014;Hébert, 2011;Liang, Williams, & Siegel, 2006;Watson & Halford, 2010). In their landmark longitudinal study, Trickett, Noll, and Putnam (2011) also pointed out that, in some cases, symptoms emerge more clearly over time, at critical periods of development.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, more severe CSA (including penetration or attempted penetration) may lead to greater traumatic sexualization and consequently to greater sexual risk behaviors that could further compromise women's sexual health (Lemieux & Byers, 2008). Some recent empirical work has also found that CSA severity as well as other covarying family dysfunction such as witnessing or experiencing childhood physical or psychological violence may be associated with the worst outcomes (Watson & Halford, 2010). Identifying which subgroups of CSA survivors are at increased risk of experiencing more adverse sexual outcomes may provide researchers and clinicians crucial information for differential prevention and intervention programs (Clemmons et al, 2003).…”
Section: Multiple Forms Of Childhood Victimization and Sexual Health mentioning
confidence: 99%